DOI: 10.11606/d.7.2017.tde-08052017-094246
|View full text |Cite
|
Sign up to set email alerts
|

Viver em situação de rua: experiência de mulheres que utilizam o albergue para pernoitar

Abstract: DEDICATÓRIAhygiene and rest. She hopes to get off the streets, get a job, get rid of drugs and prostitution, and rescue the family, however this woman remains in the situation of street because of the lack of paid work, financial gain facility in drug trafficking and prostitution, as well as the freedom which street life gives her. Final Thoughts: The findings of this study allow us to reflect that, despite the growth of policies aimed at the issues surrounding the homeless population of the streets, in practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
1
0
1
Order By: Relevance
“…Therefore, there was no agreement between the participants about which social positions would bring them more or less security. According to Biscotto (2015), violence is experienced by this group through territorial disputes, sexual practices and coexistence with drugs. Misganaw and Worku (2013) reported that body objectification makes cases of sexual abuse, sexually transmitted infections and/or pregnancy frequent, as well as causing psychic consequences.…”
Section: Copingmentioning
confidence: 99%
“…Therefore, there was no agreement between the participants about which social positions would bring them more or less security. According to Biscotto (2015), violence is experienced by this group through territorial disputes, sexual practices and coexistence with drugs. Misganaw and Worku (2013) reported that body objectification makes cases of sexual abuse, sexually transmitted infections and/or pregnancy frequent, as well as causing psychic consequences.…”
Section: Copingmentioning
confidence: 99%
“…Esta última subcategoria foi apresentada predominantemente por mulheres. Nesse sentido, algumas pesquisas (Biscotto, 2015;Campos, 2016;Rosa & Bretas, 2015) apontam que a motivação para a ida e permanência de mulheres para as ruas foi relacionada ao histórico de violências sofridas no contexto familiar, a renda insuficiente e a ruptura dos vínculos sociais. De acordo com Antoni e Muñoz (2016), o ambiente da rua é representada pela figura do homem, provedor desempregado, sendo relacionada à mulher, a imagem idealizada do ambiente doméstico, limpo, que mora em casa.…”
Section: Violência Intrafamiliarunclassified